STUDI KRITIS KONSEP PENDIDIKAN ANAK BERPERSPEKTIF GENDER - Azhari, Azhari (Tawazun: Jurnal Pendidikan Islam, 2019)
The purpose of this study is to overview of Islamic education to the children's education with a gender perspective. The method used in this thesis is a library research with a qualitative approach. Sources of data derived from primary data and secondary are presented descriptively, and then analyzed (descriptive-analytical) using the method of content analysis. The results of this study found that the concept in view of the nature of Islam (Islamic Worldview) concept of gender equality in the education of children is wrong and distorted. He deviates Islamic values based on the revelation. Because, he just saw it and ignore the temporal aspects ukhrawi aspects. Similarities and differences in the roles and status of students (male and female) are only considered as a socio-cultural construct and a product of history that can change with the times. Therefore, the concept was born from the understanding of feminism is essentially violated the creation of nature and the nature of the child who basically has the diversity and differences. He also ignores the very basic educational materials for the development of the child's personality, such as faith education, emotional, and education-intellectual reasoning. Abstrak Tujuan penelitian ini adalah untuk menganalisis tinjauan pendidikan Islam terhadap pendidikan anak berperspektif gender. Metode yang digunakan dalam penelitian tesis ini adalah studi pustaka (library research) dengan pendekatan kualitatif. Sumber data berasal dari data primer (primary sources) dan sekunder (secondary sources) yang dipaparkan secara deskriptif, kemudian dianalisis (deskriptif-analitik) dengan menggunakan metode analisis isi (content analysis). Dalam pandangan alam Islam (Islamic Worldview) konsep kesetaraan gender dalam pendidikan anak adalah keliru dan menyimpang. Ia menyelisihi nilai-nilai ajaran Islam yang berdasar pada wahyu. Sebab, ia hanya melihat aspek duniawi saja dan mengabaikan aspek ukhrawi. Persamaan maupun perbedaan peran dan kedudukan anak didik (laki-laki dan perempuan) hanya dianggap sebagai konstruksi sosial-budaya dan produk sejarah yang dapat berubah-ubah mengikuti perkembangan zaman. Oleh karena itu, konsep yang lahir dari paham feminisme tersebut hakikatnya menyalahi fitrah dan kodrat penciptaan anak yang pada dasarnya memiliki keberagaman dan perbedaan. Ia juga mengabaikan materi pendidikan yang sangat mendasar bagi perkembangan kepribadian anak, seperti pendidikan keimanan, emosional, dan pendidikan nalar-intelektual.